Розвиток методології фінансового планування - Кіртока, Р.Г. (Культура народов Причерноморья, 2014)
У статті проаналізовано існуючі моделі і методи середньострокового прогнозування бюджетних доходів і витрат, наведено їх порівняльна характеристика. Використання таких моделей, що володіють добре вивченими статистичними властивостями, дозволяє мати надійне джерело короткострокових (до року) прогнозів по доходах. Показано, що моделі середньострокового прогнозування істотно відрізняються від короткострокових моделей, оскільки середньострокові моделі повинні вміти вловлювати взаємозв'язок між фінансовою політикою (фінансовими рішеннями) і макроекономічними умовами в середньостроковій перспективі. Обґрунтовано, що важливою вимогою при розробці та впровадженні будь-якої середньострокової методології прогнозування є забезпечення послідовності та системності. В статье проанализированы существующие модели и методы среднесрочного прогнозирования бюджетных доходов и расходов, приведена их сравнительная характеристика. Использование таких моделей, обладающих хорошо изученными статистическими свойствами, позволяет иметь надежный источник краткосрочных (до года) прогнозов по доходам. Показано, что модели среднесрочного прогнозирования существенно отличаются от краткосрочных моделей, поскольку среднесрочные модели должны уметь улавливать взаимосвязь между финансовой политикой (финансовыми решениями) и макроэкономическими условиями в среднесрочной перспективе. Обосновано, что важным требованием при разработке и внедрении любой среднесрочной методологии прогнозирования является обеспечение последовательности и системности. The paper analyzes existing models and methods for medium-term forecasting budget revenues and expenditures, given their comparative characteristics. The use of such models with the well-studied statistical properties, allowing you to have a reliable source of short-term (one year) forecasts of income. Medium-term earnings forecasts are built in the medium-term macroeconomic model. Such forecasts are by nature generally less accurate than short-term It is shown that the medium-term forecasting models differ significantly from short-term models as medium model must be able to capture the relationship between financial policy (financial decisions) and macroeconomic conditions in the medium term. The basic requirements for the design and implementation of any medium-term forecasting methodology. It is proved that an important requirement when designing and implementing any medium forecasting methodology is to provide a coherent and systematic. Proved that in the practical use of a particular method requires: depth study sequential combination of quantitative and qualitative analysis, the possibility of a combination of several methods.